2021
DOI: 10.1101/cshperspect.a040113
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Lamina

Abstract: Lamins interact with a host of nuclear membrane proteins, transcription factors, chromatin regulators, signaling molecules, splicing factors, and even chromatin itself to form a nuclear subcompartment, the nuclear lamina, that is involved in a variety of cellular processes such as the governance of nuclear integrity, nuclear positioning, mitosis, DNA repair, DNA replication, splicing, signaling, mechanotransduction and -sensation, transcriptional regulation, and genome organization. Lamins are the primary scaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 211 publications
0
40
0
Order By: Relevance
“…Given that the lamin meshwork forms a scaffold for the attachment of genomic DNA packaged into chromatin, it is possible that substitutions at R264 disrupt such contacts [19,[23][24][25]. To test for this, we analyzed the degree to which the fluorescent DAPI signal colocalized with the fluorescent signal from antibodies to LamC and lamDm 0 using the JACoP plugin for Fiji [68,69].…”
Section: Larval Body Wall Muscle-specific Expression Of R264q and R264w Did Not Affect Motility But Caused Pupal Lethalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Given that the lamin meshwork forms a scaffold for the attachment of genomic DNA packaged into chromatin, it is possible that substitutions at R264 disrupt such contacts [19,[23][24][25]. To test for this, we analyzed the degree to which the fluorescent DAPI signal colocalized with the fluorescent signal from antibodies to LamC and lamDm 0 using the JACoP plugin for Fiji [68,69].…”
Section: Larval Body Wall Muscle-specific Expression Of R264q and R264w Did Not Affect Motility But Caused Pupal Lethalitymentioning
confidence: 99%
“…Lamins serve multiple functions in the cell. They provide structural support for the nucleus and ensure the integrity of the nuclear envelope [19,20]. Support for this statement comes from studies showing that transient nuclear rupture and increased DNA damage are observed in skeletal muscle nuclei, which experience mechanical stress [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle cells possess structural components to withstand such force, including high expression levels of A-type lamins, lamins A and C ( Swift et al, 2013 ; Cho et al, 2017 ). Lamins, intermediate filaments that line the inner nuclear membrane, provide structural support for the nucleus, determine the nuclear shape, and organize genomic DNA for proper gene expression ( Goldman et al, 2004 ; Burke & Stewart, 2006 ; Swift et al, 2013 ; Zwerger et al, 2013 ; Camozzi et al, 2014 ; Dialynas et al, 2015 ; Kim et al, 2017 ; Wong et al, 2022 ). Dominant mutations in the LMNA gene encoding the A-type lamins, A and C, cause Emery-Dreifuss muscular dystrophy, limb-girdle muscular dystrophy type 1B, and congenital muscular dystrophy ( Bonne et al, 1999 ; Rankin & Ellard, 2006 ; Astejada et al, 2007 ; Worman & Bonne, 2007 ; Lu et al, 2011 ; Maggi et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In higher eukaryotes, the most prominent structural component of the INM is the nuclear lamina (NL), a protein meshwork lining the NE (Burke and Stewart, 2013; Dobrzynska et al, 2016; Gruenbaum and Foisner, 2015; Wong et al, 2021). The backbone of the NL comprises polymers of nuclear lamins, type V intermediate filament proteins (de Leeuw et al, 2018).…”
Section: Introductionmentioning
confidence: 99%